Estimating tree height based on tree crown from UAV imagery / Suzanah Abdullah ... [et al.] - Abdullah, Suzanah; Tahar, Khairul Nizam; Abdul Rashid, Mohd Fadzil; Osoman, Muhammad Ariffin (Universiti Teknologi MARA, Perak, 2022)
Tree crown delineation is a significant measurement for forest inventory and management purposes. The increasing availability of high-resolution Unmanned Aerial Vehicle (UAV) data makes it possible to delineate the tree crown of a single tree. Currently, with the advancement in technology UAV has become one of the emerging technologies that offers an affordable, cheaper, and faster technology in acquiring data for numerous applications. More importantly, this technology is embedded with efficient approaches for real-time acquisition of high resolution to produce three-dimensional (3D) information. UAV images provide an accurate digital surface model for planting application. In this study, the UAV technology is explored by applying several algorithms approach to determine tree crown and tree height of a single tree canopy. As a result, this study has obtained the tree crown from the Digital Surface Model (DSM) that is filtered locally based on pixel size using the selected algorithms. Subsequently, the tree height has been calculated based on the tree crown extraction. As a conclusion, this study has contributed to the knowledge extension in this area and presented the result of the tree height values according to the segmentation algorithm at the different flying height data.